CATHOLIC SYNODALITY: A WAY TO UNITY THROUGH INTERCULTURAL EXCHANGE (Hekima Review, 2023)
Various recent synodal processes in the Catholic Church reveal the importance of reflecting on how to deal with cultural plurality. This article discusses how the Catholic Church could learn from the synodal life in Orthodox and Protestant Churches. An important difference to the mostly regional synods of these ecumenical partners is the need for a global Catholic synodality that strengthens the worldwide unity of the Church. Therefore, an intercultural perspective is necessary for a Catholic concept of synodality that aims at honouring the local, inculturated expressions of the faith.